(Not) Being cared for in hospital settings: patients’ experience from Foucault’s perspective - Débora Thais Siqueira Soares; Maria Ribeiro Lacerda; Ana Paula Hermann (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to understand patients’ experience of (lack of) care in hospital settings from Foucault’s perspective. Methods: this is the partial result of research using Grounded Theory as a methodological framework, in light of Michel Foucault’s theoretical framework. Data collection was carried out with 30 participants. Results: theoretical concepts “enjoying safe care” emerged, composed of subconcepts “receiving safe care” and “feeling safe to engage in care”, and “identifying unsafe care”, with subconcepts “recognizing risks” and “feeling insecure”. Final Considerations: by amplifying patients’ voice, it was possible to capture their needs and reflect on which aspects are a reference of (in)security for them. Understanding the relations of power, knowledge and discipline in hospital settings, in light of Foucault, highlighted the complexity of interactions in care provision, favoring leading role and empowering patients for their care.